ANALISIS FISIKOKIMIA, MIKROBIOLOGI DAN SENSORI TERHADAP PRODUK KUE PUTU AYU SUBSTITUSI TEPUNG UBI JALAR UNGU (IPOMOEA BATATAS L.) - Rahmadhania, Zira; Aulia, Ghina; Dujanah, Siti; Hashinah, Zulfa; Kurniauli, Nanda; Fauzan, Muhammad Zein; Khairunnisa, Khairunnisa; Nurtiana, Winda (Universitas Sultan Ageng Tirtayasa, 2025)
Putu ayu is one of the traditional cakes that is very popular among Indonesians. Most of the main ingredients used to make it are wheat flour and coconut milk. The use of wheat flour in the country continues to increase in line with the development of the food industry and the diversification of processed products. The high demand for wheat flour in Indonesia does not match the country's production capacity, so it remains heavily dependent on wheat imports. This high dependence on imported raw materials necessitates a strategy to reduce wheat flour usage. One step that can be taken is to utilize local food ingredients as an alternative substitute, such as purple sweet potato flour. Based on the substitution effect on product characteristics, various analyses were conducted, including physicochemical tests measuring fat, protein, moisture, ash, and starch content to evaluate the nutritional composition and chemical properties of putu ayu. Physical tests involved color measurement using a chromameter to assess visual changes due to anthocyanin content in purple sweet potato flour. To ensure food safety and product shelf life, microbiological tests were also conducted, including Total Plate Count (TPC) to determine the total number of microorganisms in the sample. Additionally, hedonic tests using the de Garmo method were conducted to determine the best sample formulation preferred by panelists or consumers. The results of this study are as follows: moisture content on a dry basis (Db) of 83.31%, ash content of 1.29%, fat content of 8.87%, protein content of 4.306%, starch content of 13.10%, chromameter color test of 5.985 (Purple/Violet), Total Plate Count (TPC) test of 2.9 x 10⁴ CFU/mL, and the hedonic test using the De Garmo calculation method yielded the best formulation of 50g wheat flour and 13g purple sweet potato flour (213) with a score of 0.895, ranked first and preferred by 37 untrained panelists.